PENGARUH KUALITAS PELAYANAN, PENANGANAN KOMPLAIN DAN CITRA PERUSAHAAN TERHADAP KEPERCAYAAN PELANGGAN PADA PT. RINA JAYA GARMENT KOTA SUKOHARJO - Bunga Maharani Utami; MG. Sukamdiani; Retnoning Ambarwati (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to determine the effect of service quality, complaint handling and company image on customer trust in PT. Rina Jaya Garment, Sukoharjo City. The scope of this study concerns the marketing management course. This research is a type of quantitative research. The population of this study is consumers of PT. Rina Jaya Garment Sukoharjo. The sample in this study is consumers of PT. Rina Jaya Garment Sukoharjo, using non-probability sampling or also called non-chance, is a purposive sampling and is subjective (Indrawan & Yaniawati, 2017). The sample in this study was 100 people. The collection technique used in this study was the distribution of questionnaires. Data analysis techniques were carried out using SPSS. Keywords : he influence of service quality, complaint handling and company image, customer trust